Maqashid syariah perspektif Imam Asy-Syathibi dan Jasser Auda - Shandana, Imasandia Nur (Maliki Interdisciplinary Journal, 2024)
Islamic regulation uncovered by Allah is, as a matter of fact, taking maslaha (benefits) and keeping away from evil (jalbul mashali hwadarul mafasid). At the end of the day, God lays out law and order to support man himself. dharuriyyat (essential), hajiyyat (auxiliary), and tahsinat (tertiary). Maqashid Sharia is something that should exist to understand the advantage of religion and the world. If not, it will cause harm and even death toll and lives like sitting, drinking, asking, fasting and other love. The five maqashid sharia recipients include: religion (al-commotion), soul (al-nafs), posterity (an-nasl), property (al-mal) and qal (al-aql). The method for safeguarding the last five can be sought after in two ways: by safeguarding its structure (minnahiyyati al-wujūd) by securing and keeping up with parts of protecting structure and non-presence (min nahiyyati al 'adam) by forestalling the things that cause its nonappearance.